Inflation hedging with South African common stocks: a JSE sectoral analysis - Kawawa, Dennis (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2019)
Inflation risk erodes purchasing power, redistributes wealth from lenders to borrowers and threatens investor's long-term objectives, which are often specified in real terms; financial market volatility presents an additional risk for investors and portfolio managers concerned with not only real returns but also absolute returns. Understanding key investment risks, of which inflation is one, is crucial for investment managers in order to design effective hedging strategies to preserve wealth over the long run. Empirical tests of the Fisher hypothesis in South Africa have shown that common stocks are a good hedge against inflation. However, empirical evidence from developed countries has also shown that the relationship between common stocks and inflation is heterogeneous across the sectors and industries. This paper analysed the sectoral differences in the hedging ability of South African common stocks to test for this heterogeneity. The paper presents disaggregated sector models to test heterogeneity across the eight sectors of the JSE securities exchange. Understanding which of these sectors offers the best hedge against inflation is important to investors, allowing them to place money where the value will be best preserved during times of higher inflation. The disaggregated sectors tested included the Basic Materials price index, Industrials price index, Consumer Goods price index, Health Care price index, Consumer Services price index, Telecommunications price index, Financials price index, and Technology price index. Johansen Cointegration techniques were employed to empirically test the Fisher hypothesis for the South African market. For the Fisher hypothesis to hold, this paper was required to find evidence of cointegration between the share indices and CPI, as well as a positive slope coefficient for the cointegrating regression. The results of the cointegration test showed that the All Share index and each of disaggregated sector indices were cointegrated with CPI. This implied that a long run relationship exists between common stocks and inflation. Two techniques were used to estimate the cointegrating regressions for each model, a standard long-run cointegrating regression normalizing on the share index and a Vector error correction model (VECM). For all the models both techniques reveal a positive relationship between common stock and CPI with the coefficients for the long run cointegrating regression derived from the various models ranging between 1.41 "“ 3.62 while the coefficients from the VECM ranged from 1.42 - 4.85. The varying coefficients provide evidence of the heterogeneity of the hedging ability of common stocks. Overall the evidence from the long run cointegration regression suggests that in times of high inflation investors are most compensated for changes in inflation in common stocks relating to the Consumer Services and Health Care sectors, but that in general all sectors of the JSE provide some hedge for inflation. The results suggest that investors are compensated for changes in inflation if they invest in specific industries rather than in the All Share index, thus diversifying portfolios could provide a better hedge for inflation. Although positive coefficients were found the weak exogeneity test revealed only technology Index was caused by changes in CPI. The Paper concluded that in the long run all sectors provided protection against inflation during the period of study, but the evidence only fully supports the Fisher hypothesis for the Technology index, due to the results of the weak exogeneity test that revealed that CPI is weakly exogenous only in the equation of the Technology index.
Keywords: Johannesburg Stock Exchange; Inflation (Finance) -- South Africa; Hedging (Finance)-- -- South Africa